From spiritualistic toward more pragmatic pattern: re-ordering Balinese houses and viability of the household traditions in tourism economy - Putra, I Dewa Gede Agung Diasana; Lozanovska, Mirjana; Fuller, Robert (Journal of Architecture and Urbanism, 2019)
The traditional Balinese house, manifested and translated in an agricultural context, has roles to accommodate domestic and socio-cultural activities. Once the house accommodates tourist activities as an additional function, many parts of the house are transformed. The transformation presents a conflict between economic gain and the preservation of Balinese traditions in the house. In order to illustrate this paradoxical phenomenon, this paper first shows how the traditional house has been reconfigured as a response to address the specific challenges of the tourist economy. Then, using architectural examination and interviews, the paper shows that the infiltration of the tourist activities has blurred the house’s configuration so that the transformed house is no longer able to express its original characteristics, hierarchy values and symbolic meaning.